Biomechanics of skeletal muscles - Zatsiorsky, V. M.; Prilutsky, B. I. (Human Kinetics, 2012)
Biomechanics of Skeletal Muscles is an essential resource for those seeking advanced knowledge of muscle biomechanics. Written by leading experts Vladimir Zatsiorsky and Boris Prilutsky, the text is one of the few to look at muscle biomechanics in its entirety—from muscle fibers to muscle coordination—making it a unique contribution to the field.